SURABI MILA: KEUNIKAN DAN POTENSI DALAM PENGEMBANGAN WISATA KULINER BANDUNG - Yayan Pratama (Yayasan Nusa Cendekia Global, 2025)
The development of the tourism industry can provide opportunities for tourism products including culinary in the city of Bandung. The high development of the tourism industry, providing an enormous opportunity for the people, to participate in the development of culinary tourism, which is currently still very limited, the amount. his paper aims to explain traditional food as a local culinary type of Surabi Mila as a tourist attraction of Bandung. Data collection was done by observation and interview. The results of this paper explain that the traditional food of local culinary Surabi Mila, is a kind of traditional food tourist attraction